2008
DOI: 10.2111/06-077.1
|View full text |Cite
|
Sign up to set email alerts
|

Soil Depth and Climatic Effects on Desert Vegetation Dynamics

Abstract: Soil depth effects on honey mesquite (Prosopis glandulosa Torr) cover and density and perennial grass standing crop were evaluated over an 11-yr period (1995-2005) on two lightly stocked and two conservatively stocked pastures on the Chihuahuan Desert Rangeland Research Center in south-central New Mexico. These four adjoining pastures have similar size, vegetation, and soils. Soils in these study pastures are primarily light sandy loams varying from a few centimeters to 1 m or more in depth underlain by a calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
2
9
0
Order By: Relevance
“…Soil depth is a potentially important niche axis promoting plant co‐existence in rocky environments: individual species and even whole communities are restricted to specific soil depths (Oosting & Anderson ; Bliss & Cox ; Baskin & Baskin ; Houle & Phillips ; Fuhlendorf & Smeins ; Porembski ; Khumalo et al. ). Such zonation is the result of interspecific differences in hydrological responses and interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Soil depth is a potentially important niche axis promoting plant co‐existence in rocky environments: individual species and even whole communities are restricted to specific soil depths (Oosting & Anderson ; Bliss & Cox ; Baskin & Baskin ; Houle & Phillips ; Fuhlendorf & Smeins ; Porembski ; Khumalo et al. ). Such zonation is the result of interspecific differences in hydrological responses and interactions.…”
Section: Introductionmentioning
confidence: 99%
“…However, some extreme data values were as high as 20% canopy cover (Ibid). Other studies conducted in the Chihuahua desert have found very similar values (Khumalo et al, 2008;Ludwig et al, 2000).…”
Section: Canopy Coversupporting
confidence: 63%
“…The Front Range of the north–south‐trending Rocky Mountains has east–west‐trending valleys, with generally NF and SF aspect hillslopes. Aspect is known to impact soil‐water content, soil hydraulic properties, and soil depths (Casanova et al, 2000; Khumalo et al, 2008; Geroy et al, 2011). Aspect affects soil development and properties in the area of the 2010 Fourmile Canyon Fire, as shown by Birkeland et al (2003), because SF aspects are warmer and drier while NF aspects are colder and wetter in general (Veblen and Lorenz, 1991).…”
Section: Field Areamentioning
confidence: 99%